2022
DOI: 10.3847/1538-4357/aca529
|View full text |Cite
|
Sign up to set email alerts
|

On the Presence of Metallofullerenes in Fullerene-rich Circumstellar Envelopes

Abstract: The presence of neutral C60 fullerenes in circumstellar environments has been firmly established by astronomical observations as well as laboratory experiments and quantum-chemistry calculations. However, the large variations observed in the C60 17.4 μm/18.9 μm band ratios indicate that either additional emitters should contribute to the astronomical infrared (IR) spectra or unknown physical processes exist besides thermal and UV excitation. Fullerene-based molecules such as metallofullerenes and fullerene-ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 29 publications
(41 reference statements)
2
20
0
Order By: Relevance
“…First, we consider the analysis of the individual mid-IR spectra for the different metallofullerenes, tracking the particular spectral features that define the metal-C 60 cage interaction for each case. To facilitate comparison, Figures 1-4 (representing all individual neutral and charged endo-and exohedral metallofullerenes spectra) also include the total (summed) spectrum for each metallofullerene species, constructed similarly to our previous work (Barzaga et al 2023). The IR intensities of the individual simulated spectra are scaled to the same total value.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, we consider the analysis of the individual mid-IR spectra for the different metallofullerenes, tracking the particular spectral features that define the metal-C 60 cage interaction for each case. To facilitate comparison, Figures 1-4 (representing all individual neutral and charged endo-and exohedral metallofullerenes spectra) also include the total (summed) spectrum for each metallofullerene species, constructed similarly to our previous work (Barzaga et al 2023). The IR intensities of the individual simulated spectra are scaled to the same total value.…”
Section: Resultsmentioning
confidence: 99%
“…Calculations of the neutral/charged endo-(inside C 60 ) and exohedral (outside C 60 ) metallofullerenes have been performed in the framework of density functional theory (DFT) at the B3LYP/ 6-31G(d) level (Ditchfield et al 1971;Becke 1993), with the Gaussian 16 code (Frisch et al 2016), following the settings reported in our previous work (Barzaga et al 2023). 9 The mid-IR spectra were obtained under the harmonic oscillator approximation, and subsequently, wavelengths were adjusted using double scaling factors to account for anharmonicity, vibrorotational coupling, and so on.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Distorting the carbon cage by ionization or adsorption of foreign atoms or groups could reduce the symmetry and introduce more active infrared features. In fact, fullerenes undergo complicated chemical processing during stellar evolution, making the formation of hydrogenated fullerenes, fullerene-metal and fullerene-hydrocarbon complexes possible (Kroto & Jura 1992, Cami 2014, Zhang et al 2020, Hou et al 2023, Barzaga et al 2022, Omont 2016. Due to its high spectral resolution and unprecedented sensitivity, the advent of the James Webb Space Telescope (JWST) offers a valuable opportunity to detect fullerene derivatives through their vibrational bands.…”
Section: Introductionmentioning
confidence: 99%